In vitro evaluation of fungitoxicity of selected natural products on heavy inoculum and conidial germination of Fusarium moniliforme - V. KURUCHEVE*, A. MATHAN, P. BALABASKAR and (Indian Phytopathology, 2008)
Certain selected natural products were screened under in vitro conditions for their fungitoxicity against Fusarium moniliforme. The results revealed that neem leaf extract (60%), buffalo urine (20%) and poultry litter (40%) concentration were able to inhibit the mycelial growth of F. moniliforme. Also, these products inhibited four 11 mm fungal discs of the pathogen (heavy inoculum) in a Petri plate. In case of spore germination neem leaf extract 40%, buffalo urine 20%, poultry litter 40% recorded total inhibition of spore germination.